Bandgap Engineering of Conjugated Nanoporous Poly‐benzobisthiadiazoles via Copolymerization for Enhanced Photocatalytic 1, 2, 3, 4‐Tetrahydroquinoline Synthesis under Visible Light. Issue 16 (2nd June 2016) - Wang, Zi Jun; Ghasimi, Saman; Landfester, Katharina; Zhang, Kai A. I.
Abstract: Conveniently combining properties such as high interfacial surface area, excellent visible light absorption and semiconductor‐range bandgap, conjugated nanoporous polymer networks are promising candidates as pure organic, metal‐free, visible light‐responsive and heterogeneous photocatalysts. Here, a facile yet precise bandgap engineering strategy to achieve fine justification of the valence and conduction band positions of a series of nanoporous polymers to optimally bracket the redox potential of the targeted individual photoredox reaction via copolymerization of the electron‐withdrawing benzobisthiadiazole moieties into the polymer network backbone is presented. The enhanced photocatalytic activity of the nanoporous polymer networks was demonstrated in the synthesis of 1, 2, 3, 4‐tetrahydroquinoline, an important motif in pharmaceutical compounds, via photooxidative cyclization of N, N ‐dimethylanilines with maleimides. Abstract :